Three phenotypes of adult‐onset asthma. Issue 5 (17th April 2013) - Amelink, M.; de, S. B.; de, J. C.; van, P. M. B.; van, P. I.; Krouwels, F. H.; Lutter, R.; Zwinderman, A. H.; Weersink, E. J. M.; ten, A.; Sterk, P. J.; Bel, E. H.
Abstract Rationale Adult‐onset asthma differs from childhood‐onset asthma in many respects. It is more heterogeneous, often severe and frequently associated with loss of lung function. To identify underlying mechanisms of adult‐onset asthma and to capture predictors of disease progression, detailed characterization and phenotyping is necessary. Objectives To characterize adult‐onset asthma and identify subphenotypes of adult‐onset asthma. Methods A cohort of 200 patients with adult‐onset (>18 year) asthma (age 54 (26–75) year) was recruited from one academic and three nonacademic pulmonary outpatient clinics in Amsterdam, the Netherlands. These patients were fully characterized with respect to clinical, functional and inflammatory markers. After data reduction, K‐means nonhierarchical cluster analysis was performed to identify clusters of adult‐onset asthma. Measurements and main results Patients with adult‐onset asthma were predominately female (61%) and nonatopic (55%). Within this group of patients were identified three clusters of adult‐onset asthma. Cluster 1 (n = 69) consisted of patients with severe eosinophilic inflammation‐predominant asthma and persistent airflow limitation despite high‐intensity anti‐inflammatory treatment, with relatively low symptom scores. The second cluster was characterized by obese women with frequent symptoms, high healthcare utilization and low sputum eosinophils. The third cluster consisted of patients with mild‐to‐moderate, well‐controlled asthma with normal lung function and low inflammatory markers. Repeatability accuracy was 98.2%. Conclusions Amongst patients with adult‐onset asthma, three subphenotypes can be identified with distinct clinical and inflammatory characteristics. These subphenotypes help to understand the underlying pathobiology and provide clinicians with directions for personalized management.